Analysis of Decision of The Medan Religious Courts About The Heir That Have Different Religion - Siti Mujiatun (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The division of inheritance according to islam, remains on similiarty of aqidah ie islam